2020
DOI: 10.2147/ndt.s241497
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evidence for a Beneficial Effect of Oral N-acetylcysteine on Functional Outcomes and Inflammatory Biomarkers in Patients with Acute Ischemic Stroke</p>

Abstract: Purpose: Numerous preclinical studies have demonstrated the potential neuroprotective effects of N-acetylcysteine (NAC) in the treatment of brain ischemia. Accordingly, the present study aimed to assess the potential therapeutic effects of oral NAC in patients with acute ischemic stroke. Patients and Methods: In a randomized, double-blind, placebo-controlled trial study, 68 patients with acute ischemic stroke with the onset of symptoms less than 24 hours were randomly assigned to either the NAC-treated group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…In fact, NAC not only does not increase the risk of infections but also, through regulatory actions on the immune system, may decrease the risk of infections [33]. Furthermore, it is well-known that NAC against acute cardiovascular and neurological events, such as myocardial infarction and stroke, has protective effects [47,48]; this effect may also be helpful for some patients at an increased risk of cardiovascular and neurological complications associated with COVID-19 [49,50]. Moreover, one of the main properties of NAC that makes it a proper candidate in preventing and treating COVID-19 is its excellent safety and tolerability even when used in high doses.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, NAC not only does not increase the risk of infections but also, through regulatory actions on the immune system, may decrease the risk of infections [33]. Furthermore, it is well-known that NAC against acute cardiovascular and neurological events, such as myocardial infarction and stroke, has protective effects [47,48]; this effect may also be helpful for some patients at an increased risk of cardiovascular and neurological complications associated with COVID-19 [49,50]. Moreover, one of the main properties of NAC that makes it a proper candidate in preventing and treating COVID-19 is its excellent safety and tolerability even when used in high doses.…”
Section: Discussionmentioning
confidence: 99%
“…Acrolein-mediated damage after stroke has been implicated in the size of strokes in animal studies and NAC has been shown to reduce the size of the infarct [ 117 ]. In a recent randomized double-blind placebo-controlled trial using NAC 4 grams four times a day for 72 hours at the onset (within 24 hours) of an ischemic stroke, the follow-up National Institute of Health Stroke Scale at 90 days resulted in a better outcome profile in both neurological deficit and disability [ 118 ].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…However, after ischemic stroke the level of endogenous antioxidants decreases, leading to oxidative stress. When patients with acute ischemic stroke were treated with a neuroprotective drug N-acetylcysteine, serum levels of SOD and glutathione peroxidase significantly increased, whereas the National Institute of Health Stroke Scale scores decreased ( Sabetghadam et al, 2020 ). Other drugs were also shown to regulate antioxidant levels and exert neuroprotective effects in animal models of cerebral ischemia.…”
Section: Mechanisms Of Ferroptosis In the Pathogenesis Of Ischemic Strokementioning
confidence: 99%